Exemplary Values From Umar Bin Khattab and Sayyidah Aisyah R.A. - Anisa Oktaviana; Siti Ardianti; Jeesica Shinta (MAQOLAT: Journal of Islamic Studies, 2023)
This journal discusses the exemplary values ​​of Umar bin Khattab and Sayyidah Aisyah RA, two important figures in Islamic history. Umar bin Khattab is known as one of the best caliphs in Islamic history, while Sayyidah Aisyah RA was one of the wives of the Prophet Muhammad who had a major influence on Islamic history. Both of them also set an example in terms of sincerity and determination in facing trials and tests. Umar bin Khattab, for example, always put the interests of the people above his own interests, while Sayyidah Aisyah RA always tried to maintain her chastity and honor, even though she faced slander and accusations that were not true. This study aims to explore exemplary values ​​that can be learned from the lives and inspirational stories of these two figures. The method used in this study is a library search by collecting information relevant to the research topic through searching and analyzing information sources such as journals, books, articles and other documents related to the topic under study. The results of the study show that these two figures have many exemplary values ​​that can be used as role models by Muslims. Some of these values ​​include integrity, courage, simplicity, fairness, sincerity, perseverance, and tolerance. In the context of modern life, the exemplary values ​​of Umar bin Khattab and Sayyidah Aisyah RA can be an inspiration for Muslim individuals to develop strong character, good work ethics, and superior leadership qualities. This research is expected to provide a better understanding of the exemplary values ​​of these two figures and their relevance in the context of modern life.